Making Climate Leadership Meaningful: Energy Research as a Key to Global Decarbonisation. Issue 2 (6th February 2015) - Karlsson, Rasmus; Symons, Jonathan
Abstract: This article revisits a number of familiar debates about climate change mitigation yet draws some unorthodox conclusions. First, that progress towards a renewable small‐scale energy future in environmentally conscious countries such as Germany and Sweden may take the world as a whole further away from climate stability by reducing the political pressure to finance breakthrough innovation. Second, that without such game‐changing innovations, developing countries will continue to deploy whatever technologies are domestically available, scalable and affordable, including thermal coal power in most instances. Third and finally, that as any realistic hope of achieving climate stability hinges on the innovation of breakthrough technologies, the urgency of climate change calls not so much for the domestic deployment of existing energy technologies but rather a concentrated effort to develop technologies that will be adopted globally. These arguments imply that national innovation policy, and an international treaty establishing a 'Low‐Emissions Technology Commitment' should be the central focus of climate policy. Abstract : In order to be meaningful, national climate policy in those states that are most committed to climate action should be formulated with a view to contributing to a global transition to a decarbonised economy.